Approaches to Representing Social Hierarchy Level and Social Constructs: Methodological Exploration and Recommendations. Issue 1 (21st May 2020) - Weeks, Matthew; Estes, Madeline
Abstract: Recent social psychological investigations on the social hierarchy have largely occurred without clear delineations in the language used to reference the different strata in the hierarchy (e.g., upper‐class vs. rich vs. high socioeconomic status [SES]). Both within and between research reports, labels can be used inconsistently. We report four studies comparing social hierarchy category labels (SHCLs) on empirically relevant dimensions. Study 1 examined the subjective SES associated with different SHCLs and found that, despite considerable similarity in terms at both the lower and upper ends of the hierarchy, substantive differences occurred. Study 2 examined perceptions of group entitativity and found that pairs of SHCLs (e.g., Rich/Poor vs. Upper‐/Lower‐Class) differ in judgment‐relevant properties. Study 3 compared four types of SHCLs on dimensions of power, status, and resources. Finally, Study 4 provided an experimental demonstration of the impact of interchanging SHCLs. Implications of the findings and recommendations for ongoing empirical efforts are discussed.